Employee’s Perspective views on the Influence of Interiors in Endorsement of Business at Themed Restaurants - A. Arun , Ali A. Alalmai (International Journal of Advanced Science and Technology, 2020)
Theme restaurant is booming phase of hospitality industry it constitutes a defined and specific decor. The effectiveness and the theme of ambience depend upon the eminence and efficiency of the interior decorations. This research work evaluates the part played by interior designing in theme restaurant to achieve their actual objective. It also involves expressing the impact of interior decoration towards the customers in promoting their business. The data are collected by conducting interviews and survey among the employees at theme restaurants, analysed with SPSS (24) software. Findings reveal that the interior decoration takes an active part in providing the blend of theme with hospitality services. It also plays an active part in self selling by attracting customers’ attention. The study concludes interior decoration has an eminent capacity in improving the business excellence of any concern.